Changes in Transfer Ribonucleic Acids Accompanying Encystment in Acanthamoeba castellanii - McMillen, Janis (1974)
Transfer ribonucleic acid (tRNA) from exponentially growing cells (trophozoites) and from precysts of Acanthamoeba castellanii were examined by reversed-phase column (RPC-2) chromatography. This system gave excellent resolution of isoaccepting species of tRNA. The tRNAs for 12 amino acids were studied. A comparison of trophozoite and precyst tRNA elution profiles revealed no apparent differences in the number of isoaccepting species of alanyl-, arginyl-, asparaginyl-, glycyl-, leucyl-, lysyl-, methionyl-, phenylalanyl-, tryptophanyl-, or valyl-tRNAs. Seryl-tRNAs from trophozoites were eluted as three components, whereas precyst seryl-tRNAs were eluted as only two components. Precharged trophozoite and precyst isoleucyl-tRNAs were both eluted as single components; however, post-chromatography charging of trophozoite tRNA resulted in three components of activity for tRNA(Ile) and only one component for precyst tRNA(Ile). None of the observed changes could be attributed to differences in synthetases or to the presence of altered tRNA lacking the CCA terminus or partially degraded by nucleases. The possible significance of these observations is discussed.